BIBLIOPHILE EDITIONS AND THE EXPERIENCE OF BIBLIOPHILE PUBLISHING IN LITHUANIA - Braziūnienė, Alma (Knygotyra, 2016)
The article deals with the concept of a bibliophile edition, types and groups of these specific editions, their appearance and development in both foreign countries and Lithuania. Bibliophile publishing in Lithuania started in 1930, after the Society of 27 Book Lovers was established, with the aim of popularising book culture and disseminating the fine editions, among other aims. The ten years of the Society of 27 Book Lovers’ existence (1930–1940) saw 10 publications, which became a shining example of the European bibliophile publishing. During the International Exhibition of Modern Art and Technology, held in Paris in 1937, the book Gulbė – karaliaus pati by Viktoras Petravičius was awarded the Grand Prize, Mečislovas Bulaka’s illustrations of Liūdna pasaka by Jonas Biliūnas was awarded the Gold medal, whereas Vytautas Kazimieras Jonynas received the Gold medal for wood carvings for books and posters. During the Soviet period, not a single bibliophile edition was published in Lithuania. The authorities looked upon bibliophilic activities as a kind of the game played by the bourgeois society, alien to the Soviet people and contrary to the official Communist ideology. The publication of the first numbered editions was started only during the period of Perestroika and National Revival Movement in 1987–1988. The article aims to analyse the numbered editions published by four bibliophile organizations, currently active in Lithuania, during the last two decades as well as the publications issued by other Lithuanian publishing houses which could be regarded as bibliophilic editions. On the basis of the research, the following conclusion could be drawn: the above mentioned numbered editions, with a few exceptions, do not meet the criteria of a bibliophile edition. Therefore, one can hardy talk about the tradition of publishing bibliophile editions in the present-day Lithuania, based on the bibliophile culture, even though certain individual successful examples do exist. Even though Lithuania today boasts a number of internationally renowned book artists, the publishing houses have neither theoretical nor practical readiness to publish bibliophile editions. The bibliophile clubs active in Lithuania largely unite book lovers as amateurs rather than bibliophiles as book collectors. As such, these clubs are passive ideological supporters of bibliophile movement, exerting little influence on the appearance of new bibliophile editions. Nevertheless, the publishing activities launched by certain Lithuanian bibliophiles – book collectors, aimed at making their collections public, is sufficient proof that the ambitions of making business, book collecting and disseminating art can be successfully combined. A certain number of books, published in Lithuania recently, meet the status of a bibliophilic edition. Claiming that bibliophile publishing today is in the margins of Lithuania’s publishing activities, we have to admit that certain hopeful signs do exist nevertheless.